REVITALISASI KURIKULUM ADMINISTRASI PUBLIK DI ABAD 21 - Gedeona, Hendrikus Triwibawanto (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
Activity of curriculum renewal of Public Administration has ought to became matter that is inseparable in our life dynamics as a institution of education. It was caused by dynamic its environment change: local, regional, national and also global related to locus and focus of Public Administration. Departement of Public Administration not show interest them the same by effort will in realize to decrease quality from Departement of Public Administration, also disband its institution by itself. In consequence, face dynamics of environment change, society change, andparadigma shift of Public Administration that walk so quick, has became policy options that sine qua non for us for continuously conduct renewal to which we all majors curriculum pride upon. Until from time to time aspect of scientific and pracktical was from our Public Administration always up to date and can answer demand of environment change, even more than that can determine environment change itself.